European Non‐Invasive Trisomy Evaluation (EU‐NITE) study: a multicenter prospective cohort study for non‐invasive fetal trisomy 21 testing. (21st July 2013) - Verweij, E. J.; Jacobsson, B.; van Scheltema, P. A.; de Boer, M. A.; Hoffer, M. J. V.; Hollemon, D.; Westgren, M.; Song, K.; Oepkes, D.
ABSTRACT: Objective: To evaluate the performance of a directed non‐invasive prenatal testing method of cell‐free DNA analysis for fetal trisomy 21 (T21) by shipping the whole blood samples from Europe to a laboratory in the USA. Methods: A European multicenter prospective, consecutive cohort study was performed enrolling pregnant women from Sweden and the Netherlands. Blood samples were drawn just prior to a planned of invasive diagnostic procedure in a population at increased risk for fetal T21 and then shipped to the USA without any blood processing. Chromosome‐selective sequencing was carried out on chromosome 21 with reporting high risk or low risk of T21. Karyotyping or rapid aneuploidy detection was used as the clinical reference standard. Results: Of the 520 eligible study subjects, a T21 test result was obtained in 504/520 (96.9%). Risk assessment was accurate in 503/504 subjects (99.8%). There was one false negative result for T21 (sensitivity 17/18, 94.4%, and specificity 100%). Conclusion: This is the first prospective European multicenter study showing that non‐invasive prenatal testing using directed sequencing of cell‐free DNA applied to blood samples shipped across the Atlantic Ocean, is highly accurate for assessing risk of fetal T21. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? After a decade of research, a clinically applicable technology was developed for non‐invasive testing of fetal chromosomal anomalies, using sequencing of cell‐free DNA fragments in maternal plasma. In many countries, however, this new development is not yet available. What does this study add? The European non‐invasive trisomy evaluation study shows that shipping the whole blood samples across the Atlantic Ocean, using a directed cell‐free DNA approach for analysis is an accurate and feasible option for European women.